2011
DOI: 10.1159/000331725
|View full text |Cite
|
Sign up to set email alerts
|

Amoxapine Inhibits Delayed Outward Rectifier K<sup>+</sup> Currents in Cerebellar Granule Cells via Dopamine Receptor and Protein Kinase A Activation

Abstract: Background: Although tricyclic antidepressants amoxapine is proposed to target 5-HT and D2 receptors, very few studies have addressed the effect of amoxapine on molecular and cellular mechanisms via receptor pathways. In this study, we test the effect of amoxapine on rat cerebellar granule neurons (CGNs) to address this possibility. Methods: CGNs cell culture, whole-cell current recording using a patch-clamp technique, western blot and non-radioactive detection analysis of phosphorylated protein kinase A (PKA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…We obtained robust 3D-QSAR models when we included potassium, calcium and, especially iron ions, augmented by water. Our results are in agreement with experimental studies [31][32][33][34] indicating that the presence of iron, calcium or potassium ions is critical for antagonistic effects of psychiatric drugs at membrane receptors. Additionally we point that the effectiveness of antidepressants and antipsychotics is enhanced more by potassium and iron than by sodium.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We obtained robust 3D-QSAR models when we included potassium, calcium and, especially iron ions, augmented by water. Our results are in agreement with experimental studies [31][32][33][34] indicating that the presence of iron, calcium or potassium ions is critical for antagonistic effects of psychiatric drugs at membrane receptors. Additionally we point that the effectiveness of antidepressants and antipsychotics is enhanced more by potassium and iron than by sodium.…”
Section: Discussionsupporting
confidence: 92%
“…Potassium and sodium ions are essential for all living cells, being especially important for neuron function, and for osmotic balance between cells and interstitial fluid. 32,38 Calcium homeostasis, especially in the context of the central nervous system, has crucial implications under many neuropsychiatric conditions. 30,31 It was reported that antipsychotic medication was not effective unless serum calcium and magnesium levels were both normal.…”
Section: Almond Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, our data suggest that GLP-1R activation suppresses delayed rectifier potassium channel-mediated currents, rather than rapidly inactivating potassium currents, which results in the depolarization of the membrane potential. Previous studies showed that the cAMP-PKA pathway could suppress delayed rectifier K v channels (5,23,24,(52)(53)(54)(55); our work suggests that the GLP-1R activationinduced reduction of K v can also be controlled by cAMP-PKA activity. Thus, our data indicate that the signaling pathway involved in the GLP-1 regulation of DMH neurons can progress as follows: An elevation in intracellular cAMP levels activates PKA signaling, which leads to the blockade of the delayed rectifier potassium channel, resulting in postsynaptic neuronal depolarization and excitation (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…It is a potent inhibitor of glycine transporters GLYT1b and GLYT2a [Núñez et al 2000], and it activates delta-opioid receptors in human frontal cortex in vitro [Onali et al 2010]. In addition, amoxapine has been shown to inhibit several K + channels including the voltage-gated K + [He et al 2010] and the G protein-activated inwardly rectifying K + (GIRK) channels [Kobayashi et al 2011] at micromolar concentrations, the same range as the brain concentration of the drug during treatment (5-67 μM); this effect seems to be mediated through serotonin and dopamine D1/D5 receptors [Yang et al 2011].…”
Section: Introductionmentioning
confidence: 99%